Ochotona hyperborea - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Ochotona hyperborea (Pallas, 1811). Zoogr. Rosso-Asiat., 1:152. TYPE LOCALITY: ". e terris Tschuktschicis," [Chukotsk peninsula (Ognev, 1940:41), Chukotsk A.O., Russia]. DISTRIBUTION: Ural, Putorana, Sayan Mtns, east of Lena River to Chukotka, Koryatsk and Kamchatka; upper Yenesei, Transbaikalia, and Amur regions, Sakhalin Island (Russia); NC Mongolia; NE China; N Korea; Hokkaido (Japan). STATUS: Appears common throughout its large range. SYNONYMS: cinereoflava (Schrenk, 1858); coreana Allen and Andrews, 1913; ferruginea (Schrenk, 1858); kamtschaticus Dybowski, 1922; kobayashii Kishida, 1930; kolymensis Allen, 1903; litoralis Peters, 1882; mantchurica Thomas, 1909; normalis (Schrenk, 1858); sadakei Kishida, 1933; svatoshi Turov, 1924; turuchanensis Naumov, 1934; uralensis Flerov, 1927; yezoensis Kishida, 1930; yoshikurai Kishida, 1932. COMMENTS: Formerly incuded in alpina; see A. T. Smith et al. (1990), and references therein. Difference in morphology and vocalizations are noticeable where hyperborea and alpina are sympatric in the W Sayan Mtns, Khangai Mtns, and Transbaikalia, and character displacement in size is also evident in some populations (A. T. Smith et al., 1990). The original citation was printed and privately circulated in 1811, but not published for general distribution until 1826. Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 809, DOI: 10.5281/zenodo.7353088